Pola Komunikasi Guru Pendidikan Anak Usia Dini (Studi Kasus Pada PAUD Bahrul Ulum ) Pulau Balang Caddi Kel. Mattiro Bintang Kab. Pangkep - Anggriani Amir; Fitri Rezkiamaliah; Anugrah Murtini (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
Early childhood education is an important foundation and foundation for children to continue their lives in the future. In the research conducted, the authors wanted to find out how the communication patterns of early childhood education teachers and what factors were the supports and obstacles in the communication process of early childhood education teachers in KB. Bahrul Ulum Balang Caddi Island Kel. Mattiro Bintang Kec. Liukang Tupabbiring Kab. Pangkep. The method used in research in KB. Bahrul Ulum Balang Caddi Island Kel. Mattiro Bintang Kec. Liukang Tupabbiring Kab. Pangkep is a case study that seeks to explain in more detail with this type of descriptive research. The approach used is the approach of sociology, communication, psychology, and religion with the stages of research namely observation, interviews, and documentation, then using data analysis techniques. So that it can be seen how the communication patterns of early childhood education teachers and what factors support and hinder the communication process of early childhood education teachers in KB. Bahrul Ulum Balang Caddi Island Kel. Mattiro Bintang Kec. Liukang Tupabbiring Kab. Pangkep. This study uses teaching and learning theory. Based on the findings at the research location, the authors can conclude that the communication patterns that are often used are one-way communication patterns and two-way communication patterns. Supporting factors in the communication process are the existence of adequate facilities, teaching aids, and very good textbooks students need. While the inhibiting factors in the communication process are the barriers of the communication process, physical barriers, semantic barriers and psychological barriers.